E-Government Framework and Modeling in Denpasar - Evi Triandini; Candra Ahmadi (Jurnal Eksplora Informatika, 2011)
At its core E-Government is the use of information technology that can improve the relationship between the government and other parties. Within which involve automation and computerization of the paper-based procedures that exist that will encourage new ways of leadership, new ways of discussion and define strategies, new ways in business transactions, new ways of listening to citizens, and communities, as well as new ways of organizing and delivering information. The main prerequisite for an e-government is the IT infrastructure investments should be managed (well-managed), selected, controlled, and focused on the support of missions that generally improve organizational performance and reduce costs. if these prerequisite investments can be a burden for the organization's performance. Often a large IT infrastructure investments within the scope of government, is still hampered by operational data accuracy and discrpancies of the system. However, at present there is general agreement that the government's ability to improve services and organizational performance can be helped how big the role of IT infrastructure investments that can be utilized. Computer are now obsolete should be replaced frequently; process with an inefficient paper orientation should be automated; financial data / accurate budget should be maintained, and a lot of information and be on the increase must be stored and managed.